2011
DOI: 10.1038/cr.2011.148
|View full text |Cite
|
Sign up to set email alerts
|

Specific lectin biomarkers for isolation of human pluripotent stem cells identified through array-based glycomic analysis

Abstract: Rapid and dependable methods for isolating human pluripotent stem cell (hPSC) populations are urgently needed for quality control in basic research and in cell-based therapy applications. Using lectin arrays, we analyzed glycoproteins extracted from 26 hPSC samples and 22 differentiated cell samples, and identified a small group of lectins with distinctive binding signatures that were sufficient to distinguish hPSCs from a variety of non-pluripotent cell types. These specific biomarkers were shared by all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
79
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 39 publications
2
79
0
1
Order By: Relevance
“…Thus, the development of novel cell surface markers to evaluate the properties of iPSCs and ESCs is keenly required. Toward this goal, a glycomic approach has been made by several groups (17)(18)(19)(20). In our previous study using an advanced lectin microarray technique (21), thirty-eight lectins capable of discriminating between iPSCs and SCs were statistically selected, and the characteristic features of the pluripotent state were obtained.…”
mentioning
confidence: 99%
“…Thus, the development of novel cell surface markers to evaluate the properties of iPSCs and ESCs is keenly required. Toward this goal, a glycomic approach has been made by several groups (17)(18)(19)(20). In our previous study using an advanced lectin microarray technique (21), thirty-eight lectins capable of discriminating between iPSCs and SCs were statistically selected, and the characteristic features of the pluripotent state were obtained.…”
mentioning
confidence: 99%
“…Immunocytochemistry (ICC) showed that the iPSCs were positive for canonical markers of pluripotency [OCT4 (also known as POU5F1), SOX2 and NANOG] (Figure 1b) and the iPSCs differentiated via embryoid body (EB) formation expressed markers for each of the germ layers (Figure 1c) 1,3 . qPCR analyses of the iPSCs confirmed expression of pluripotency markers (Figure 1d).…”
Section: Introduction Results and Conclusionmentioning
confidence: 99%
“…In the authors' laboratory, as a lectin-based glycan profiling method, a unique lectin microarray system based on an evanescentfield activated fluorescence detection principle was developed [41,42]. With this system, we and other groups successfully profiled distinct sets of glycomes of both somatic and pluripotent stem cells [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%